Validation of the parental feeding style questionnaire in a portuguese sample - Pimenta,Filipa (2019)
Portugal is among the European countries with higher rates of overweight children, and parental feeding practices may affect children weight and eating patterns. A community sample of 252 Portuguese parents was used to study the psychometric properties of the Portuguese version of the Parental Feeding Style Questionnaire. (i.e., structural, convergent and discriminant validity, external and criterion validity, as well as reliability and sensitivity). Regarding construct validity, the measurement model supported a five-factor structure (Emotional, Instrumental, Encouragement, Permissiveness, and Control) with an acceptable fit; Item 24 was excluded since it showed a very low factor weight and was not significantly associated with its subscale (λ=0.274; p=0.065); also, this items explained variance was below the recommended (r²=0.018). Discriminant validity was verified in eight of the ten paired factors. Only the emotional eating subscale had a good value of VME (convergent validity; VME = .62). External validity was confirmed, as was internal consistency, where four of the five subscales, with the exception of the emotional eating subscale, had good Cronbach's alphas (.67 <α <.88). The Portuguese sample reported the predominant use of permissiveness and control practices, similar to that reported by previous studies. The Portuguese Parental Feeding Style Questionnaire appears valid and reliable for assessing Portuguese parents feeding styles and can be used in further studies. The existence of culturally adapted and validated instruments is fundamental for an accurate understanding of parental practices, in order to develop strategies to manage childrens dietary intake and prevent health-related problems, subsequent to overweight.